HYR, an extracellular module involved in cellular adhesion and related to the immunoglobulin-like fold - CALLEBAUT, ISABELLE; GILGÈS, DELPHINE; VIGON, ISABELLE; MORNON, JEAN-PAUL (Protein science, 2000)
Domains belonging to the immunoglobulin-like fold are responsible for a wide variety of molecular recognition processes. Here we describe a new family of domains, the HYR family, which is predicted to belong to this fold, and which appears to be involved in cellular adhesion. HYR domains were identified in several eukaryotic proteins, often associated with Complement Control Protein (CCP) modules or arranged in multiple copies. Our analysis provides a sequence and structural basis for understanding the role of these domains in interaction mechanisms and leads to further characterization of heretofore undescribed repeated domains with similar folds found in several bacterial proteins involved in enzymatic activities (some chitinases) or in cell surface adhesion (streptococcal C-alpha antigen).